2019
DOI: 10.1177/1093526619852869
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Placental Injury in Congenital Anomalies in Second Half of Pregnancy

Abstract: Background Placental pathology in fetal congenital anomalies in second half of pregnancy is largely unknown. Methods Twenty-six clinical and 45 independent placental phenotypes from pregnancies ≥20 weeks of gestation with congenital anomalies divided into 4 groups were retrospectively compared with analysis of variance or χ 2 with 3 degrees of freedom and with Bonferroni correction for multiple comparisons: group 1 : 112 cases with heart malformations (with or without chromosomal anomalies), group 2 : 41 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Although perinatal mortality, the most severe fetal pregnancy complication, is 3 times more frequent in this material of FVM than in our database of high-risk pregnancy [27], there were no statistically significant differences in this outcome rate among the 3 groups (Table I), which reflects various time intervals between the onset of FVM and delivery (temporal heterogeneity) more than etiology. We documented previously the characteristic association with mass-forming fetal anomalies and the lesions of FVM [36]. Some authors observed a trend towards more segmental FVM and higher grade FVM in cases of neonatal encephalopathy [11], but we observed intracerebral vascular thrombi even in low-grade SFVM diagnosed by CD34 immunohistochemistry only [32].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Although perinatal mortality, the most severe fetal pregnancy complication, is 3 times more frequent in this material of FVM than in our database of high-risk pregnancy [27], there were no statistically significant differences in this outcome rate among the 3 groups (Table I), which reflects various time intervals between the onset of FVM and delivery (temporal heterogeneity) more than etiology. We documented previously the characteristic association with mass-forming fetal anomalies and the lesions of FVM [36]. Some authors observed a trend towards more segmental FVM and higher grade FVM in cases of neonatal encephalopathy [11], but we observed intracerebral vascular thrombi even in low-grade SFVM diagnosed by CD34 immunohistochemistry only [32].…”
Section: Discussionsupporting
confidence: 64%
“…The lower rate of villous infarction in global FVM may be due to partial umbilical cord compromise in the etiology of this type of FVM that is known not to be associated with lesions of maternal vascular malperfusion. The same is true about the 2 features of shallow placental implantation which were previously reported in association with mass-forming fetal anomalies [36], but not with umbilical cord compromise [23]. It is difficult to explain why hypertrophic decidual arteriolopathy is more common in high-grade SFVM (Table II), particularly as there is no characteristic distribution in maternal hypertensive conditions among the 3 groups (Table I).…”
Section: Discussionmentioning
confidence: 67%
“…Other authors reported 8.7%, with a similar frequency of global and segmental FVM, with high-grade FVM more common than low-grade FVM [26]. We reported FVM in 10-24% of placentas from pregnancies complicated by congenital malformations, depending on the type of malformation, but in that material distal FVM was diagnosed traditionally based on clustered avascularity of distal villi on H&E staining (27). In the currently analysed population of high-risk pregnancies dominated by foetal congenital malformations, the prevalence of FVM was substantially higher because of expanding the inclusion criteria (endothelial fragmentation and hypovascularity by CD34, and segmental villous mineralization in addition to clusters of sclerotic distal villi and clusters of villi with stromal vascular karyorrhexis).…”
Section: Discussionmentioning
confidence: 49%
“…The absence of statistically significant differences in many clinical or placental phenotypes between Groups 1 and Group 2, but also among all 3 groups, indicates that FVM is only one of the patterns of placental injury having an impact on the foetal condition in this specific type of pathology dominated by frequently severe foetal congenital anomalies. Previously we reported that foetal anomalies in the second half of pregnancy show abnormal clinical phenotypes much more frequently than abnormal placental phenotypes, the mass-forming anomalies featuring diffuse chronic hypoxic patterns of placental injury and lesions of FVM, which are probably stasis-induced [27]. Our current material obtained in the Children's Hospital contained few hypertensive conditions of pregnancy, diabetes mellitus, infections, chronic FHR abnormalities, genetic thrombophilia, FGR, and oligohydramnios, i.e.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation